DIAGNOSTIC ACCURACY OF MRI IN DIAGNOSIS OF FUNGAL SINUSITIS TAKING HISTOPATHOLOGY AS GOLD STANDARD (The Research of Medical Science Review, 2025)
OBJECTIVE:To determine the diagnostic accuracy of MRI in detecting fungal sinusitis using histopathology as the gold standard. MATERIALS AND METHODS:A cross-sectional study was done at the Department of Radiology, General Hospital, Lahore.The duration of the study was six months. For sample, Non-Probability Consecutive Sampling technique was used. A sample of 97 cases was calculated using 95% confidence limit, percentage of fungal sinusitis as 30%, and sensitivity and specificity of MRI as 85% and 83% with 13% margin of error. Inclusion criteria included patients of suspected fungal sinusitis referred from ENT department for MRI face to investigate possible sinus pathology, patients’ age 20 to 60 years and patients of either gender. Data analysis was done using Software SPSS. Data was stratified on age, gender, BMI, duration of symptoms and post-stratification test was used to assess statistical significance with p<0.05 as statistical significant. RESULTS:This study demonstrated that MRI is a highly sensitive tool for detecting fungal sinusitis, with a sensitivity of 93.59%. However, its specificity was moderate at 52.63%, meaning some cases identified as positive on MRI were later found to be negative on histopathology. The most commonly involved sinus was the maxillary sinus (58 cases), and MRI was particularly effective in detecting bone erosion and intraorbital spread. CONCLUSION:MRI is a valuable non-invasive imaging tool with high sensitivity for diagnosing fungal sinusitis. However, its moderate specificity suggests that histopathology remains the gold standard for definitive diagnosis. Future studies with larger sample sizes and advanced imaging techniques may further improve diagnostic accuracy